Protective association of A-T-T haplotype of DMT1 gene against risk of human age-related nuclear cataract - Sankaranarayanan, Rajkumar; Vidya, Nair Gopinathan; Vasavada, Abhay Raghukant (Ophthalmic genetics, 2019)
Age-related cataract (ARC) is profoundly associated with oxidative stress. Iron plays a pivotal role in generating oxidative stress and promoting deleterious irreversible damage to the macromolecules. Divalent metal transporter 1 (DMT1) mediates the uptake of iron into the cell. Aberrant transcript expression of DMT1 gene in lenses of human ARC was reported. The present investigated the genetic association between DMT1 gene polymorphisms and risk of ARC. DNA from peripheral blood of ARC subjects (n = 764) and age-matched controls (n = 794) was isolated. Genotyping of three single-nucleotide polymorphisms (SNPs) - rs224589 (C/A), rs1048230 (T/C), and rs2285230 (T/C) - of DMT1 gene was performed by polymerase chain reaction (PCR)-restriction fragment length polymorphism technique. Level of DMT1 transcript expression was determined by quantitative real-time PCR analysis using RNA from lens epithelial and fiber cells. Nuclear cataract showed a higher frequency of CC genotypes (OR = 1.40; 95%CI = 1.01-1.95; p = 0.04) of SNP rs224589 and a significantly lower frequency of A-T-T haplotype (OR = 0.63; 95%CI = 0.42-0.92; p = 0.02) than that of controls. The A-T-T haplotype demonstrated a dominant protective effect against disease risk when compared to the more common haplotype (C-T-T) (p = 0.01). The haplotype pairs C-T-T/C-T-T and A-C-C/A-C-C showed higher level of transcript expression of DMT1 than C-T-T/A-T-T haplotype pair (p < 0.05). Further, a novel genetic variation (c.1328A>G; p.N443S) in exon 3 of DMT1 gene was observed in a subject with nuclear cataract. The results highlighted a protective association of A-T-T haplotype against the risk of ARC.